Quality management in healthcare: The pivotal desideratum - Anubha Aggarwal; Himanshu Aeran; Manu Rathee (Journal of Oral Biology and Craniofacial Research)
Health care is very complex sector and delivery of service is the fragmented care. Quality can be a common paradigm to address the need of all groups in health care. Quality improvement is the process approach to the organization’s operational challenges. The initiative to address the quality in health care has become a global phenomenon. A quality revolution for delivery of service with patient at the center and services around it is the demand of the time. This article comprehensively reviews the quality management in health care service and aims to sensitize the health care professionals towards achieving total quality.